Preparation and characterization of calcium oxide from crab shells (Portunus pelagicus) and its application in biodiesel synthesis of waste cooking oil, palm and coconut oil - Minaria Minaria; Risfidian Mohadi (Science and Technology Indonesia, 2016)
Preparation of calcium oxide from Portunus pelagicus through thermal decomposition for 3 hours at various temperature 700°C, 800°C,900°C,1000°C, and 1100°C. The calcium oxidefrom decomposition was carried out and characterized by X-Ray Diffractometer (XRD), FT-IR spectrophotometer and SEM-EDX analyses. The result of XRD show decomposition Portunus pelagicus at 1000°C have diffraction pattern agree with the CaO diffraction standard with 2θ value 32.4º, 37.5º, 64.3º, and 67,5º. The FT-IR spectrum show vibration of CaO at wavenumber 354.9 cm-1. SEM-EDX data indicated the surface morphology calcium oxide of Portunus pelagicus more homogen than Portunus pelagicus before decomposition. The decomposition of CaO at 1000°C was applied in the syntesis of biodiesel from waste cooking oil, palm oil, and coconut oil. The biodiesel products have density 0.8621, 0.8725, and 0.8688 g/cm3. Viscosity are 5.27, 3.71, and 2.45 mm2/s(cst). Acid values respectively are 0.3069, 0.2423 and 0.2100 mg/KOH and Iodine numbers 39.48, 36.12 and 9.24 g I2/100g. All characteristic of biodiesel from waste cooking oil, palm oil, and coconut oil are agree with SNI standard. The best biodiesel product derived from coconut oil is agree to the parameter value of biodiesel standard. Keywords: biodiesel. Portunus pelagicus. calcium oxide. catalyst.